2005
DOI: 10.1037/0002-9432.75.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Homeless Near a Thousand Homes: Outcomes of Homeless Youth in a Crisis Shelter.

Abstract: Clients who received crisis services at a homeless shelter for transition-aged youth were recruited for a study to describe the youth served, to track outcomes of care, and to examine factors associated with differing outcomes. Participants were 202 men and women who completed a battery of interviews and self-report measures at intake and at 3 follow-up points. Youth served had experienced high levels of adversity and trauma and typically had poor educational and vocational preparation. A multidisciplinary arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Although not focused on transitions away from homelessness specifically, there are some longitudinal quantitative studies of homeless youth that have examined days housed in a given period of time-a variable that is relevant to the process of exiting homelessness (Barber et al, 2005;Slesnick, Kang, Bonomi, & Prestopnik, 2008, Slesnick, Bartle-Haring, Dashora, Kang, & Aukward, 2008Milburn et al, 2009;Rosenthal et al, 2007;Tevendale, Comulada, & Lightfoot, 2011;Roy et al 2004). While the methods and findings of these studies vary considerably, there are some consistent themes.…”
Section: Pathways Out Of Homelessnessmentioning
confidence: 90%
“…Although not focused on transitions away from homelessness specifically, there are some longitudinal quantitative studies of homeless youth that have examined days housed in a given period of time-a variable that is relevant to the process of exiting homelessness (Barber et al, 2005;Slesnick, Kang, Bonomi, & Prestopnik, 2008, Slesnick, Bartle-Haring, Dashora, Kang, & Aukward, 2008Milburn et al, 2009;Rosenthal et al, 2007;Tevendale, Comulada, & Lightfoot, 2011;Roy et al 2004). While the methods and findings of these studies vary considerably, there are some consistent themes.…”
Section: Pathways Out Of Homelessnessmentioning
confidence: 90%
“…Four studies evaluated the effectiveness of shelters in alleviating symptoms associated with the youth’s stay at the shelter (Barber, Fonagy, Fultz, Simulinas, & Yates, 2005; Pollio, Thompson, Tobias, Reid, & Spitznagel, 2006; Steele & O’Keefe, 2001; Thompson, Pollio, Constantine, Reid, & Nebbitt, 2002). Adolescents who received shelter services reported reduced days on the run, school and employment problems at six weeks post-discharge (Thompson et al, 2002; Pollio et al, 2006), reduced behavioral and emotional problems at six months (Barber et al, 2005), and reduced substance use at discharge (Steele & O’Keefe, 2001).…”
Section: Service Evaluationsmentioning
confidence: 99%
“…Adolescents who received shelter services reported reduced days on the run, school and employment problems at six weeks post-discharge (Thompson et al, 2002; Pollio et al, 2006), reduced behavioral and emotional problems at six months (Barber et al, 2005), and reduced substance use at discharge (Steele & O’Keefe, 2001). These authors also reported a lack of improvement in several realms.…”
Section: Service Evaluationsmentioning
confidence: 99%
“…For example, some homeless youth maintain connections with parents, build relationships with other significant adults who play a mentoring role in their lives (e.g., agency staff) and/or participate in the activities of a religious institution (Johnson et al 2005). Additionally, homeless youth may seek to move away from the street economy by going to work or attending school (Barber et al 2005).…”
Section: Introductionmentioning
confidence: 98%